2019
DOI: 10.12659/ajcr.911399
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Persistence of Normal Tissue Oxygenation Monitored by Near-Infrared Spectroscopy (NIRS) Values Despite Prolonged Perioperative Cardiac Arrest

Abstract: Patient: Male, 65Final Diagnosis: Aortic dissectionSymptoms: Hemiplegia • hypotensionMedication:—Clinical Procedure: Emergent surgerySpecialty: SurgeryObjective:Mistake in diagnosisBackground:Patients undergoing cardiac surgery are at risk of adverse perioperative neurological complications. Cerebral oximetry monitoring is increasingly used in these patients to detect intraoperative cerebral hypoxia or ischemic events. Near-infrared spectroscopy (NIRS) uses the near-infrared region of the electromagnetic spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Moreover, external factors such as cerebrospinal fluids or blood in the subarachnoid or subdural space may have an effect on the measurements [9,30]. Moreover, it has been shown that NIRS can monitor normal cerebral oxygenation values in patients with brain death [32,11,33]. It has been hypothesized that normal rSO2 during prolonged cardiac arrest may be the result of the absence of cerebral metabolism, preservation of the extracranial circulation (NIRS device is significantly influenced by the oxygenation of the scalp and skull), or a maintained residual cerebral perfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, external factors such as cerebrospinal fluids or blood in the subarachnoid or subdural space may have an effect on the measurements [9,30]. Moreover, it has been shown that NIRS can monitor normal cerebral oxygenation values in patients with brain death [32,11,33]. It has been hypothesized that normal rSO2 during prolonged cardiac arrest may be the result of the absence of cerebral metabolism, preservation of the extracranial circulation (NIRS device is significantly influenced by the oxygenation of the scalp and skull), or a maintained residual cerebral perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are several limitations to this analysis. Firstly, there are a lot of factors related to the treatment of a serious condition which may affect the monitored signals and parameters, even though they represent the real critical care environment: analgesia, sedatives, intravenous anaesthetics, and nursery manoeuvres [32]. Moreover, as it has been shown in previous research, the value of rSO 2 may be influenced by the depth and type of administered anaesthesia, the systemic arterial blood pressure, haematocrit, arterial carbon dioxide partial pressure (P a CO 2 ), arterial oxygen saturation (SaO 2 ), pH and temperature [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…In a small cohort of 7 neurocritical care patients, 2 of whom had a TBI, Kim et al (2010) and colleagues found that changes in HgO and total hemoglobin were not significantly correlated with CBF as measured by Xenon CT. Shafer et al (2011) found similar results in a study of 22 patients, 3 of whom had TBI. It is clear that the relationship between rSO 2 and CBF is more complex as has been demonstrated in a recent case report of persistent normal rSO 2 during prolonged cardiac arrest (Maillard et al, 2019). This might possibly be explained by reduced metabolic demand resulting in the maintenance of cerebral oxygen levels in the absence of CBF.…”
Section: Cerebral Blood Flowmentioning
confidence: 91%
“…Since 70-80% of the blood in the brain is in the venous compartment, NIRS mainly reflects venous blood oxygenation, but the rScO2 value represents the weighted average of tissue oxygenation. In other words, it shows the balance between oxygen need and oxygen delivery rather than oxygen delivery 2,5 . There are other devices developed to evaluate tissue oxygenation that use different techniques.…”
Section: Monitoring Cerebral Oxygenationmentioning
confidence: 99%